Reduction of Vibrations in Long-Span Continuous Girder Bridges with Pounding Tuned Mass Dampers - Juncheng Yao; Hekuan Zhou; Jiahua Zhu; Liang Huang; Jianguo Xu; Weiguo Li (Advances in Civil Engineering)
Earthquakes often cause bridges to vibrate to different degrees; moreover, in the case of poor road conditions, the vibration amplitude of bridges caused by vehicles often exceeds a reasonable range, thus causing different degrees of damage to bridges. Therefore, this article studies the vibration reduction effect of the pounding tuned mass dampers (PTMD) on long-span continuous bridges under earthquake and vehicle loads. The PTMD used in this study can reduce the vibration in both lateral and vertical directions. The PTMD provides a stronger vibration dampening effect compared to the TMD since it increases collision to use energy. The LS-DYNA software is used for numerical modeling to optimize the parameters of the PTMD and to determine the size and installation position of the PTMD. Then, the bridge is subjected to two recorded ground motions, and the bridge response with and without the PTMD is compared and analyzed, which shows how PTMD might lessen bridge vibration in its transverse direction. To assess how efficiently the PTMD dampens vibrations induced by vehicle loads on bridges, a vehicle/bridge/PTMD system is simulated using a refined vehicle model. The findings demonstrate that the PTMD may significantly lessen the bridge’s lateral and vertical vibration while enhancing driving comfort. Thus, this research study is of great significance for vertical and lateral vibration control of long-span continuous girder bridges.